Exogenous application of melatonin mitigates salt stress in soybean - Oliveira, Pablo Henrique de Almeida (2024)
Salinity is an abiotic factor that impairs the growth and physiological, biochemical, and molecular mechanisms of plants. Among plants, soybeans are an important crop worldwide, so managing abiotic factors is essential to mitigate plant damage. However, biostimulants, such as melatonin, are being employed to alleviate the stress caused by these factors. Therefore, this study aimed to evaluate the growth, photosynthetic pigments, and water relations of soybean plants subjected to salinity levels and exogenous melatonin application. The research was conducted in experimental area belonging to the Federal Rural University of the Semi-Arid Region, Mossoró, RN, Brazil. The experimental design was randomized blocks, arranged in a 3 x 3 factorial scheme (three salinity levels in the irrigation water – 0.50, 3.00, and 5.00 dS m-1 and three melatonin concentrations – 0, 0.5, and 1 mM) with three replications. At 47 days after planting, plant height, stem diameter, number of leaves, root length, chlorophyll content (a, b, and total), relative water content, leaf moisture, and electrolyte leakage                 were evaluated. Soybean plants tolerated the effects of salinity on growth aspects, photosynthetic pigments, and water relations up to 3.00 dS m-1, regardless of melatonin concentration. Exogenous application of melatonin mitigated the effects of salt                             stress on chlorophyll b and relative water content at salinity level of 5.00 dS m-1 and concentration of 1 mM.